THE PRINCIPLE OF CONCEPTUALITY IN PROJECTS OF ADAPTATION AND ADJUSTMENT TO CONTEMPORARY NEEDS OF REVITALIZED HISTORICAL HERITAGE SITES - Romana Vasylivna Kiuntsli; Andriy Volodymyrovych Stepanyuk; Iryna Vasylivna Besaha (теорія та практика дизайну)
Abstract. Objective. The aim of this study is to analyze the role and impact of the principle of conceptuality in the process of revitalizing, adapting, and adjusting abandoned architectural heritage sites of Eastern Europe to modern needs. The research focuses on determining how conceptual approaches can enhance the efficiency and quality of architectural-spatial solutions in such projects. Methodology. Various scientific methods were employed to achieve the objective. First, graph-analytical methods were applied to analyze revitalization and adaptation projects of Eastern European heritage sites. Second, a comparative analysis was conducted on the typological features of historical buildings, structures, and complexes. Third, the current state of buildings, their structures, and architectural- historical complexes was assessed using a natural research method. Finally, structural analysis was used to identify the relationships between elements of the architectural- spatial structure of buildings and the factors influencing them. Additionally, a study and analysis of literary sources on conceptual and adaptive architecture were undertaken. Results. The study revealed that conceptual design plays a key role in the execution of architectural-spatial solutions for the revitalization and adaptation of buildings, structures, and historical heritage complexes. Specifically, the project execution process, aimed at the rational use of existing environments, must include an initial stage – the search for a conceptual idea. This approach leads to more effective and aesthetically accomplished solutions for revitalization tasks. The results also confirm that the application of the principle of conceptuality allows for better adaptation of revitalized spaces to modern societal needs. Scientific novelty. For the first time, the influence of conceptuality on the processes of adaptation and revitalization of Eastern European architectural heritage has been thoroughly examined. A new approach has been proposed to explore the role of concepts in architectural solutions, which allows for greater efficiency in project execution. This research expands the understanding of how conceptual design can contribute to the preservation and adaptation of historical sites in contemporary conditions. Practical significance. The results of this study can be used by architects and specialists in the field of restoration and adaptation of architectural objects to enhance the effectiveness of revitalization projects. They can also serve as a methodological basis for further research in this area, as well as be useful in educational programs preparing specialists in architecture and cultural heritage preservation.